PENGARUH AUDIT TENURE, UKURAN AUDITOR, SPESIALISASI AUDIT DAN AUDIT CAPACITY STRESS TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang listed di BEI tahun 2010-2015) - Kurniawansyah, Deddy (Universitas Airlangga, 2016)
The purpose for this research is totest audit tenure, auditor size, auditspecialization industry, and audit capacity stress to earning managementmanufacture industry listed in the BEI in 2010-2015. In this research, we useleverage, firms size, and ROA as Control variable. This study population wasmanufacture industry listed in the BEI in 2010-2015. This population use criteriapopulation by 703 annual reports manufacture industy. The sampling used in thisstudy a sensus method. Source of data is secondary data, obtained from annualreports of manufacture industry in BEI. This study used multiple regretion analysisto analysis data with the help of the program Partial Last Square (PLS). The resultsobtained in this study is audit tenure, and audit capacity stress has a positive effecton earning management manufacture industry. Auditor size, and auditspecialization industry has a negative effect onearning management manufactureindustry. For control variable, the results obtained is leverage, firms size, and ROAhas a positive effect on earning management manufacture industry. The resultsprovide more informed basis for investors to be more selective in investing theirfunds. To reduce earnings management practices in companies should principalsswitched auditorsperiodically or less than 3 years, and using scale big fourauditors, and has specialized audit industry